2002
DOI: 10.1046/j.0306-5251.2001.bjcp1558.doc.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital prescribing errors: epidemiological assessment of predictors

Abstract: Aims To demonstrate an epidemiological method to assess predictors of prescribing errors. Methods A retrospective case-control study, comparing prescriptions with and without errors. Results Only prescriber and drug characteristics were associated with errors. Prescriber characteristics were medical specialty (e.g. orthopaedics: OR: 3.4, 95% CI 2.1, 5.4) and prescriber status (e.g. verbal orders transcribed by nursing staff: OR: 2.5, 95% CI 1.8, 3.6). Drug characteristics were dosage form (e.g. inhalation devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 30 publications
4
86
0
5
Order By: Relevance
“…25 In a study by Finji, drug dosage was not mentioned in 63% of the examined prescriptions. 30 In 98.08% of the examined prescriptions in the present study, the identity of the physician was mentioned. In a study on prescription writing skill among two groups of dentists, 98.1% of the prescriptions written by the first group and 22.8% of the prescriptions written by the second group had the dentist's signature; furthermore, 46.3% of the prescriptions written by the first group and 15.8% of the prescriptions written by the second group had medical system code as well.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a study by Finji, drug dosage was not mentioned in 63% of the examined prescriptions. 30 In 98.08% of the examined prescriptions in the present study, the identity of the physician was mentioned. In a study on prescription writing skill among two groups of dentists, 98.1% of the prescriptions written by the first group and 22.8% of the prescriptions written by the second group had the dentist's signature; furthermore, 46.3% of the prescriptions written by the first group and 15.8% of the prescriptions written by the second group had medical system code as well.…”
Section: Discussionmentioning
confidence: 99%
“…These include errors involving omission of needed information; poor hand-writing perhaps leading to errors of drug dose or timing; and prescription of drugs that are inappropriate for the specific situation. Prescribing errors promote the irrational use of drugs and decrease patient compliance [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, British, American and Saudi studies reported that incorrect dose was the most common prescribing error (54%, 39.7% and 22.1% respectively) [6,8,29]. Similarly, a 14-day study in teaching hospitals in Netherlands indicated the dosing errors (dose/duration) was the most common prescribing error type (63%) [19]. Therefore, among the reviewed studies in the literature, our study had the second highest percentage of drug-drug interaction errors.…”
Section: Discussionmentioning
confidence: 98%
“…There was only one Iraqi study measuring medication errors by 2014 and this was an observational study (without interventions) which evaluated the types and medication classes of these errors [18]. Although several studies have investigated pharmacist interventions in prescribing errors around the world [6,8,[19][20][21][22][23][24][25], almost all of these studies were limited to evaluations of the incidence rate, causes, clinical significance and types of prescribing errors. However, a little is known about physician acceptance rate of pharmacist recommendations and only a couple of studies have focused on implementation of recommendations [26,27].…”
Section: Introductionmentioning
confidence: 99%